2011
DOI: 10.1007/s00213-011-2473-3
|View full text |Cite
|
Sign up to set email alerts
|

Blunted vagal reactivity predicts stress-precipitated tobacco smoking

Abstract: Rationale Long-term smoking can lead to changes in autonomic function, including decreased vagal tone and altered stress responses. One index of the inability to adapt to stress may be blunted vagal reactivity. Stress is a primary mechanism involved in relapse to smoking, but mechanisms leading to stress-precipitated relapse are not well understood. Objectives Using an experimental paradigm of stress-precipitated smoking behavior, we examined whether autonomic reactivity mediates the relationship between str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 82 publications
(129 reference statements)
4
42
1
Order By: Relevance
“…While parasympathetic inputs facilitate humans to respond flexibly to stressors, sympathetic dominance is associated with maladaptive behaviors (Cyranowski et al, 2011). For instance, blunted vagal reactivity may predict the ability to resist smoking in abstinent smokers (Ashare et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While parasympathetic inputs facilitate humans to respond flexibly to stressors, sympathetic dominance is associated with maladaptive behaviors (Cyranowski et al, 2011). For instance, blunted vagal reactivity may predict the ability to resist smoking in abstinent smokers (Ashare et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, breathing may help to relax smokers and thus counteract common withdrawal symptoms. For instance, acute alterations in sympathovagal activity and blunted vagal reactivity are linked to cessation (Ashare et al 2012), and drugs inhibiting sympathetic activity have been shown to decrease withdrawal symptoms (Sofuoglu et al 2003). It has been hypothesized that voluntary slow deep breathing functionally resets the autonomic nervous system through stretch induced inhibitory signals and hyperpolarization currents in both neural and nonneural tissue which synchronizes neural elements in the heart, lungs, limbic system and cortex (Jerath et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…23 It seems that stress-precipitated, decreased vagal reactivity predicts the ability to resist smoking; findings suggest that strategies, which normalize vagal reactivity in early abstinent smokers, may lead to improved smoking-cessation outcomes. 24 The balancing effectiveness of auriculotherapy on vagal regulation has been shown in some studies. 25 Therefore, there is a neurophysiologic basis for using auriculotherapy to achieve smoking cessation and to sustain smoking remission.…”
Section: Methodsmentioning
confidence: 98%